2003
DOI: 10.1002/jbm.a.20011
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast function on nanophase alumina materials: Influence of chemistry, phase, and topography

Abstract: Alumina is a material that has been used in both dental and orthopedic applications. It is with these uses in mind that osteoblast (bone-forming cell) function on alumina of varying particulate size, chemistry, and phase was tested in order to determine what formulation might be the most beneficial for bone regeneration. Specifically, in vitro osteoblast adhesion, proliferation, intracellular alkaline phosphatase activity, and calcium deposition was observed on delta-phase nanospherical, alpha-phase convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 27 publications
8
84
0
1
Order By: Relevance
“…The Ca/P composition ratio of the mineral-like tissue was 1.63 which corresponds well with the biological hydroxyapatite value (Figure 7b). These results show that mineralization was not affected by the ZnAl 2 O 4 composition of the films and the mineral deposition enhance was in concordance with previous studies of zinc-containing biomaterials that had shown an osteoconductive material for bone-related tissue engineering applications [40][41][42][43] .…”
Section: Resultssupporting
confidence: 92%
“…The Ca/P composition ratio of the mineral-like tissue was 1.63 which corresponds well with the biological hydroxyapatite value (Figure 7b). These results show that mineralization was not affected by the ZnAl 2 O 4 composition of the films and the mineral deposition enhance was in concordance with previous studies of zinc-containing biomaterials that had shown an osteoconductive material for bone-related tissue engineering applications [40][41][42][43] .…”
Section: Resultssupporting
confidence: 92%
“…Ball-like, bar-like, and plate-like α-Al 2 O 3 are widely used as heat-insulating materials and as reinforcements for composites [4]. Moreover, alumina is also used for dental materials or orthopedic devices because of its good biocompatibility [5][6]. Thus, the synthesis of boehmite with a given morphology has attracted considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…Later, tailoring the surface functionalities and the geometry of the scaffold garnered much attention in developing a scaffold that mimics the topography of the extracellular matrix. The integration of the nano-geometrical features and appropriate functional groups on the biomimetic scaffold produced better results when compared to the twodimensional cultures initially attempted [9,10,11]. This particular aspect continues to be the most investigated facet in tissue engineering at present.…”
Section: The Evolution Of Tissue Engineeringmentioning
confidence: 99%